Identification of Nanostructural and Specific Absorption Rate (SAR) on Mn0.25Fe2.75O4/Ag Nanoparticle Composites. Issue 1 (May 2019) - Miftachul Chusna, Nadiya; Sunaryono; Hidayat, Samsul; Hidayat, Nurul; Mufti, Nandang; Taufiq, Ahmad
Abstract: Mn0.25 Fe2.75 O4 nanoparticles have been successfully synthesized using the coprecipitation method. The nanoparticles are the basic components in the fabrication of Mn0.25 Fe2.75 O4 /Ag composites which have been synthesized using the chemical reduction method. To investigate the nanostructure, morphology, functional group, and specific absorption rate (SAR) value of Mn0.25 Fe2.75 O4 nanoparticles and Mn0.25 Fe2.75 O4 /Ag composites, material has been characterized using XRD, TEM, FTIR, and magneto-thermal instruments respectively. The XRD pattern showed that Mn had been successfully substituted well in the Mn0.25 Fe2.75 O4 nanoparticles indicated by the shift of diffraction peak towards the smaller angle of 2θ. Through Rietica analysis, the crystal sizes of Mn0.25 Fe2.75 O4 and Ag nanoparticles were 5.40 nm and 8.05 nm respectively. This result was confirmed well by TEM characteristics which showed that the average size of Mn0.25 Fe2.75 O4 and Ag particles as much as 5.03 nm and 8.74 nm respectively. The success of Ag nanoparticle in Mn0.25 Fe2.75 O4 /Ag composites was from the distribution of Fe-O and amine functional groups which were the representation of Mn0.25 Fe2.75 O4 and Ag nanoparticles. Furthermore, Ag nanoparticles were relatively effective in increasing the SAR value of Mn0.25 Fe2.75 O4 /Ag composites of 0.19 W/g (without Ag) into 0.21 W/g (with 0.2 g Ag).